SOCIAL NETWORKS AS A SUPPORT IN THE OLD AGE IN SPAIN - AGUDO PRADO, SUSANA; García-Sampedro, Marta (Journal of Education Culture and Society, 2020)
Aim. This article presents the results of research whose aim is to establish if social networks are useful tools to promote social relationships and support for the elderly citizens.Method. One hundred thirty people over the age of 65 participated in the research. For this purpose, the scale “elderly people and social network” (elaborated ad hoc) was applied.Results and conclusion. The results obtained through descriptive analysis of the gathered data indicate that social networks provide support for elderly people who had already acquired digital competence in the past. The study also reveals that there are personal variables, especially of an educational nature, that determine the acquisition of an active role as generators and producers of digital content (prosumers). In conclusion, it could be said that social networks have a positive influence on the well-being of the elderly and their fight against undesirable loneliness. The more heterogeneous the social network is, the more active the elderly people are.